The effect of high-frequency neuromuscular electrical stimulation training on skeletal muscle properties in mice - Valenzuela, Pedro L.; de Melo Aroeira, Andresa Evelem; Torrella, Joan R.; de la Villa, Pedro (Archives of Biological Sciences, 2017)
The aim of this study was to analyze the effects of high-frequency neuromuscular electrical stimulation training (NMES) on the structure, function and oxidative capacity of the skeletal muscle using a mice model (C57BL/6J strain, n=8). The left tibialis anterior muscle in mice was electro-stimulated (ST) whereas the right muscle was maintained as an internal control (CT). The ST limb was submitted to eight surface (100 Hz) NMES sessions in two weeks, with a minimum gap of 24 h between sessions. NMES training increased muscle mass (42.0±3.3 vs. 36.1±5.4 mg, p<0.05, effect size [ES] r=0.55), the mean fiber cross-sectional area (FCSA) (3318±333 vs. 2577±405 µ2, p<0.001, ES=0.71), maximal force (224.7±13.8 vs. 184.5±30.9 mN, p<0.01, ES=0.64), and the rate of force development (1.63±0.14 vs. 1.34±0.20 mN/ms, p<0.05, ES=0.64), with no effects on the muscle oxidative profile. These results demonstrate that surface NMES induced muscle hypertrophy and instigated an improvement in the contractile properties of the TA muscle in mice. Therefore, this animal model appears to be suitable for the study of hypertrophic processes as it enables better control of the stimulus properties (intensity, duration, frequency, etc.) than other traditionally used animal models and does not require negative reinforcements or surgical procedures. https://doi.org/10.2298/ABS160925110V Received: September 25, 2016; Revised: October 15, 2016; Accepted: October 18, 2016; Published online: November 11, 2016 How to cite: Valenzuela PL, de Melo Aroeira AE, Torrella JR, de la Villa P. The effect of high-frequency neuromuscular electrical stimulation training on skeletal muscle properties in mice. Arc Biol Sci. 2017;69(3):391-7.